Could Personal Resources Influence Work Engagement and Burnout? A Study in a Group of Nursing Staff (2020)
The aim of this research is twofold. First, to identify the role of personal resources on burnout and work engagement in nursing staff and second to evaluate whether these last two concepts are or not, opposite faces of the same construct. Personal resources are understood as individuals’ aspects that make people more confident to control their environment successfully. This study used a cross-sectional approach with a sample composed of 219 Colombian nursing personnel all of them were women. In line with our predictions, personal resources were positively related to employees’ work engagement (rxy =.40) and negatively to burnout (rxy = -.51), as well as engagement and burnout showed to be different constructs that are inversely related (rxy = -.95). The greater inverse correlation between personal resources and burnout seems to indicate that personal resources could be an important protective factor for nursing staff. Since personal resources can be developed, these findings have important implications for the human resource management in the health care settings. Due to the complexity of health work environment, further research needs to find more evidence to understand the role of personal resources in these environments. © The Author(s) 2020.